2018
DOI: 10.1016/j.jaci.2017.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and T helper cytokine–driven epithelial barrier dysfunction in allergic rhinitis

Abstract: Our data indicate a key role for allergic inflammatory mediators in modulating nasal epithelial barrier integrity in the pathophysiology in AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(177 citation statements)
references
References 58 publications
4
163
0
6
Order By: Relevance
“…We did not observe genotype effects on mRNA expression (P>0.05); however, we observed phenotype effects on mRNA expression (P<0.001) (Figure 2; Table S1). We observed mRNA expression under the "T2-Skewed" phenotype recapitulated clinical features of chronic respiratory diseases, including barrier dysfunction, 12 mucus production, 9 allergic responses, 10 and T2 responses. 47,59 We observed barrier dysfunction under the "T2-Skewed" phenotype by downregulation of Tuba1a, Tubb4a, Tjp1, Jup, and Gja1, which are markers for αtubulin, β-tubulin, tight, adherens, and gap junctions, respectively.…”
Section: The "T2-skewed" Phenotype Is An In Vitro Model Of Chronic Rementioning
confidence: 69%
See 1 more Smart Citation
“…We did not observe genotype effects on mRNA expression (P>0.05); however, we observed phenotype effects on mRNA expression (P<0.001) (Figure 2; Table S1). We observed mRNA expression under the "T2-Skewed" phenotype recapitulated clinical features of chronic respiratory diseases, including barrier dysfunction, 12 mucus production, 9 allergic responses, 10 and T2 responses. 47,59 We observed barrier dysfunction under the "T2-Skewed" phenotype by downregulation of Tuba1a, Tubb4a, Tjp1, Jup, and Gja1, which are markers for αtubulin, β-tubulin, tight, adherens, and gap junctions, respectively.…”
Section: The "T2-skewed" Phenotype Is An In Vitro Model Of Chronic Rementioning
confidence: 69%
“…1,2 Despite these economic advantages over in vivo models, in vitro models are currently limited by: 1) the use of immortalized or transformed cell lines that may not recapitulate primary cell phenotypes, 2) the use of cells from a single genetic background or phenotype, which may not capture the impact of underlying genetics or diseases on exposure risk and response variability, and 3) the limited efforts to relate in vitro exposures to occupational exposures in order to provide a regulatory basis for sensitivity to occupational exposures and inform regulatory policy aimed at special protections for all populations. 3,4 Chronic respiratory diseases, including asthma, acute bronchitis, and chronic obstructive pulmonary disease (COPD), collectively affect 16% of the United States population; these diseases impair host defense mechanisms, such as barrier function and immune regulation, 5 mucocilliary clearance and permeability, [6][7][8][9][10][11][12] as well as enzymatic and non-enzymatic regulation of oxidative stress, 13,14 and may increase an individual's sensitivity to occupational exposures. [15][16][17] Chronic respiratory diseases place a major burden on individuals, their workplaces, and the healthcare system, and yet less than 1% of the chemicals regulated by the U.S. Environmental Protection Agency's (US EPA) Toxic Substances Control Act (TSCA) have been tested for respiratory toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The next step in this study was to demonstrate this endothelial permeability by analysis of the leakage of large serum proteins like albumin (52,53). When endothelial barrier function is impaired, more albumin will leak through the airway's endothelium into the lung mucosal tissue (edema), which in turn is responsible for additional airway narrowing in asthmatics (54).…”
Section: Pde3a -/-And Pde3b -/-Mice Show Reduced Albumin Leakage In Amentioning
confidence: 99%
“…The PDE3 inhibitor cilostazol has been shown to improve barrier function by reducing leakage of albumin in vitro (55). We studied albumin leakage in both lung tissue and alveolar lumen by ELISA, which is reliable, instead of indirect Evans blue dye techniques (52,53,56). Initially, PBS-treated WT, PDE3A -/-, and PDE3B -/-mice had albumin levels that are within the normal range.…”
Section: Pde3a -/-And Pde3b -/-Mice Show Reduced Albumin Leakage In Amentioning
confidence: 99%
“…Histamine, an important mediator of allergic reactions, is implicated in the pathogenesis of allergic rhinitis. 16,17 It was reported that histamine nasal insufflation can induce nasal itch, sneezing, rhinorrhea, and nasal blockage. 18 In the current study, our data showed that PF markedly inhibited PMACI-induced histamine release in HMC-1 cells.…”
Section: Pf Prevents the Activation Of Mapk Pathway In Activated Hmmentioning
confidence: 99%